Association of worsening of nonalcoholic fatty liver disease with cardiometabolic function and intestinal bacterial overgrowth: A cross-sectional study - Lira, Marília Marques Pereira (PLoS One, 2020)
BACKGROUND & AIMS: Non-alcoholic fatty liver disease (NAFLD) has been associated with small bowel bacterial overgrowth (SIBO) and cardiometabolic dysfunction. This cross-sectional study aimed to evaluate the cardio-metabolic parameters and SIBO in patients with different degrees of hepatic fibrosis estimated by NAFLD fibrosis score (NFS). METHODS: Subjects (n = 78) were allocated to three groups: Healthy control (n = 30), NAFLD with low risk of advanced fibrosis (NAFLD-LRAF, n = 17) and NAFLD with a high risk of advanced fibrosis (NAFLD-HRAF, n = 31). Anthropometrics, blood pressure, electrocardiogram and heart rate variability (HRV) were evaluated. Only the NAFLD-LRAF and NAFLD-HRAF groups were submitted to blood biochemical analysis and glucose hydrogen breath tests. RESULTS: The NAFLD-HRAF group had higher age and body mass index when compared to the control and NAFLD-LRAF groups. The prevalence of SIBO in the NAFLD group was 8.33%. The low frequency/high-frequency ratio (LF/HF ratio) was augmented in NAFLD-LRAF (p < 0.05) when compared with control group. NAFLD-HRAF group had a wide QRS complex (p < 0.05) and reduced LF/HF ratio (p < 0.05) compared to the control and NAFLD-LRAF groups. Serum levels of albumin and platelets were more reduced in the NAFLD-HRAF subjects (p < 0.05) than in the NAFLD-LRAF. CONCLUSIONS: NAFLD impairs cardiac autonomic function. Greater impairment was found in subjects with a worse degree of hepatic fibrosis estimated by NFS. Hypoalbuminemia and thrombocytopenia were higher in subjects with a worse degree of hepatic fibrosis, whereas prevalence of SIBO positive was similar between the groups.